2013
DOI: 10.1002/acr.22014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Tests in Idiopathic Inflammatory Myopathy: Association With Clinical Parameters in Children

Abstract: Objective. To determine the association of decreased lung function in children with idiopathic inflammatory myopathies (IIMs) with specific clinical parameters. Methods. This study of 38 children ages 6 -23 years diagnosed with definite/probable IIM evaluated the association of myositis-specific/-associated antibodies (MSAs/MAAs), duration of untreated disease at diagnosis, Disease Activity Score for muscle (DAS-M), muscle-derived enzymes (aldolase, lactate dehydrogenase [LDH], aspartate transaminase, and crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Increased levels of neopterin have been reported in various clinical disorders, including several autoimmune diseases. The significant elevation of serum levels of neopterin in DM patients observed in our study are in agreement with previously published studies . In addition, we found that serum levels of neopterin correlated with disease activity in DM patients, as previously reported in juvenile myositis patients .…”
Section: Discussionsupporting
confidence: 93%
“…Increased levels of neopterin have been reported in various clinical disorders, including several autoimmune diseases. The significant elevation of serum levels of neopterin in DM patients observed in our study are in agreement with previously published studies . In addition, we found that serum levels of neopterin correlated with disease activity in DM patients, as previously reported in juvenile myositis patients .…”
Section: Discussionsupporting
confidence: 93%
“… 62 The expert group determined that all children should have assessment of lung involvement at time of diagnosis by pulmonary function tests, including carbon monoxide (CO) diffusion capacity. 63 64 Further testing is necessary in those with an abnormal restrictive pattern, preferably in collaboration with a paediatric pulmonologist. The performance of pulmonary function tests can be difficult in very young children and can also be affected by general muscle weakness.…”
Section: Resultsmentioning
confidence: 99%
“… 63 There is insufficient evidence to advise on frequency of assessment during follow-up, but physicians should be aware of the long-term risk of lung involvement especially in those with a high myositis damage index (MDI) score 62 and a regular assessment of lung function may be prudent in patients that have positive anti-RNA synthetase antibodies. 64 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, subclinical involvement of the respiratory muscles is rather frequent with a reduced total lung capacity in 26 to 78% of the patients. 14, 60,61 Dyspnea at exertion is found in up to 40% of the patients 14 and is more frequent in patients with polymyositis than in dermatomyositis or overlap syndromes. Restriction can be caused either by muscle weakness or by reduced motility of the thoracic wall.…”
Section: Lung Diseasementioning
confidence: 99%